(untitled) (Research, Society and Development, 2022)
Due to the large increase in operations and production, there has been a high production of waste in slaughterhouses in recent years, but when disordered and unsupervised, the treatment of these wastes can have harmful impacts on the environment. In this way, the study makes an evaluation of an existing Effluent Treatment Station (ETE) of a slaughterhouse in São Luís - MA, analyzing its chemical composition and comparing them to the SEMA Ordinance Nº 79/2013 of the state of Maranhão, CONAMA Resolution Nº. 430/2011 and CONAMA Resolution Nº. 357/2005. It is observed that the values of the slaughterhouse in question are close to those stipulated by CETESB, some being relatively lower, such as: oils and greases and suspended solids. However, it was possible to verify that the ETE has efficiency oscillations regarding the removal of DBO5 for the release of the effluent. As for the other analyses, inefficiency was verified in the treatment of most of the parameters, which demonstrates the operational failure of the ETE, with the need to adapt to meet the current normative legislation that regulates the release of treated effluent and the quality of the receiving watercourse.